Next generation assessment technology: the potential and pitfalls of integrating individual and community risk assessment - Byrne, James M. (Probation journal, 2017)
The recent inclusion of community-level risk variables in (some) fourth generation risk assessment instruments, ostensibly to make more accurate individual-level predictions of the likelihood of reoffending among the populations of probationers and parolees under community supervision, is examined in the following review. This development raises a thorny issue: what if the price of improved predictive accuracy is increased gender, race, or class-based disparity? Our review underscores the problems (conceptualization and measurement related) inherent in combining individual risk variables with community-level risk variables in order to assess an offender’s risk for re-offending during a specified follow-up period. In recognition of the likely disparity that will result from the conflation of neighborhood risk into individual risk assessments, we suggest an alternative: conduct a separate neighborhood risk assessment that can be used to simultaneously develop (1) a community-based treatment plan for individual offenders and (2) a resource development plan identifying and addressing service shortfalls and other risk factors in the neighborhoods where offenders reside.